Powered Solar Phone Charger Using Arduino Solar Tracker in UTHM, Pagoh - Seng Xiang, Ngien; Binti Zambri, Nor Aira; Sy Si, Sim (Progress in Engineering Application and Technology, 2023)
Solar power is one of the renewable energies that had been commonly used to replace the non-renewable energy sources such as fossil fuel since years ago. Residential customers use solar power as one of the alternative power supply to reduce dependency on non-renewable energy. Besides, solar system is also suitable for small application such as solar toy car, remote control plane and also for phone charging application that is important for the user to charge their electronic devices. There are lack of phone charging service in most university and also in UTHM campus. This phone charging station allows UTHM community to charge their electronic gadget such as mobile phone, iPad and others. The main objective of this project is to develop a free phone charging station with an automatic solar tracking system which will keep the solar panels able to track the sun direction in order to generate maximum the efficiency of the solar system. The power generated by the solar tracker system will be stored in the battery for the phone charging purposes. The system is separated into two systems which are solar tracker and phone charger systems. For the solar tracker system, it is mainly function to track maximum solar energy with the help of two LDR sensors, a servo motor and two 10 kΩ resistors. The system is controlled by using Arduino UNO in order to function as solar tracker. Based on the testing results, it can be conclude that the efficiency of the solar tracking system is higher than the static solar panel output by comparing the output voltage of both systems. At the end of the project, a powered solar phone charger using Arduino solar tracker is designed to benefits all the student in UTHM campus.